European journal of international law. - EJIL (Oxford : Oxford University Press, 1990)
The European Journal of International Law is firmly established as one of the world's leading journals in its field. With its distinctive combination of theoretical and practical approaches to the issues of international law, the journal offers readers a unique opportunity to stay in touch with the latest developments in this rapidly evolving area.
"Published on behalf of the EJIL"--Home page.
Description based on online resource; title from home page (viewed on September 28, 2016).
Keywords: International law -- Periodicals; International law -- European Union countries -- Periodicals